An integrated core training program improves joint symmetry and metabolic economy in trained runners - Gottschall, J. S.; Hastings, B. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Over 60 million Americans participate in running as a form of exercise or sport annually, making it the most popular form of physical activity in the country. Although there are numerous health benefits from a regular running routine, it is also an activity associated with a high risk of injury. Multiple factors, such as core muscle weakness and stride asymmetry, contribute to running injuries and loss of performance. The aim of this study was to assess how an integrated, functional core training intervention affects the components of performance (metabolic economy and speed) as well as a risk factor associated with injury (range of motion joint asymmetry). We hypothesized that economy, 5-km speed, and range of motion symmetry would increase in runners who added a 6-week integrated core-training intervention to their routine compared to a control group who simply maintained their current running routine. METHODS: Twelve, healthy adult runners participated in the study and six of these participants completed the exercise intervention. Heart rate data were collected to estimate metabolic economy while kinematic data were collected to calculate joint range of motion asymmetry. RESULTS: Our data demonstrated that running asymmetry decreased by a statistically significant 60% at the ankle in the sagittal plane while economy was 3% greater on both level and incline surfaces. CONCLUSIONS: In summary, runners who completed the 6-week integrated, functional training intervention improved economy, 5-km speed, and range of motion symmetry in comparison to the runners who simply maintained their current training routine.